The relationship between financial development and income inequality in Turkey - Mehmet Akif Destek; Avik Sinha; Samuel Asumadu Sarkodie (Journal of Economic Structures, 2020)
Reducing income inequality and enhancing access to financial institutions play a vital role in achieving the Sustainable Development Goal 10, especially in developing countries. While there are studies on the nexus between financial development and economic growth, literature on financial development-income inequality nexus is limited and lack consensus. This paper examined the different dimensions of financial development on income inequality for the period 1990 to 2015 in Turkey. For this purpose, four financial development indices (i.e., overall financial development index, banking sector development index, stock market development index, and bond market development index) were constructed with principal component analysis (PCA). In addition to financial development indicators, the impact of real income, government expenditures, and inflation on income inequality were investigated using the ARDL bound testing procedure. The results showed that increasing real income and govern-ment expenditures reduce income inequality. We found a positive impact of inflation on income inequality in the short run, while the reverse holds in the long run. In the case of financial development, an inverted U-shaped relationship with income inequal-ity for overall financial development and banking sector development was confirmed. A monotonically decreasing relationship between stock market development and income inequality was found in Turkey. The study highlights that the implementation of policies that eradicate discriminatory laws and facilitate equal access to financial privileges will promote equity and decline the outcomes of income inequality.
Keywords: 330; Financial development; Income inequality; Financial markets; Sustainable Development Goal 10; Turkey